Sound Problems in Interpreting: a Comparative Study of Undergraduate Program at Sebelas Maret State University - Taufik Nur Hidayat; Fedro Iswandi; Ahmad Kirom (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2017)
The study is to classify the problem triggers in consecutive interpreting especially in listening. The objectives of the research are to find out the relationship between listening skills and sound problem by comparing the test results of English student and non-English student and prove that students’ problem triggers are closely related to the writing and reading performances which are caused by listening skill problems such as domain in comprehension, similar word, etc. The method used in the research is descriptive qualitative. The participants are English Department and non English student. Technique of collecting data in the research uses questionnaire, test, and interview. The biggest problem faced by non-English student group is numbering and proper names. It is 34 % which occupy in first rank. Whereas the percentage of English student in comprehension is 27%, then the numbering and proper names, the last is similar word which has 20%. Meanwhile, the test result of English group is 84.5 and non-English group is 60. It represent the background knowledge factors are also play an important role in doing the test. In conclusion, there is relationship between students’ problem triggers, writing and reading performances, especially homophone errors. So, the hypothesis is accepted and it strengthens a currently underdeveloped theory that sounds problem play an important role in listening.